Demonstration Method in Teaching Writing and Personal Pronouns - Hastuti, Dwi Puji; Pratama, Rizky Mirani Desi; Safitri, Lia (International Journal of Research in Education, 2024)
This research aimed to evaluate the effectiveness of the demonstration technique in teaching writing and personal pronouns refer to grammar to Private High School students in Lampung. Writing is a complicated aspect of English skills, particularly for personal pronouns. Personal pronouns are used by people, animals, things, or things. These pronouns depend on the role (subject, object, or possessive), number, third-person, and gender of the replaced noun. The students admitted that the learning method they had received thus far was tedious and only confused them; they needed to learn how to distinguish pronouns in personal pronoun material. The research used a qualitative method and involved 55 students from Private High School students in Lampung, classes IX A and B. Before the demonstration method was applied, almost 50% of students' scores were below 78. The learning method they received was tedious and confusing; they needed to learn how to distinguish pronouns in personal pronouns. However, students’ performance increased or was higher after using the demonstration method. The good and excellent ranges improved to 29%, and 58% of the total was 87%. The results indicate that the demonstration technique is an effective method for teaching writing, particularly for enhancing students' understanding of personal pronouns. Hence, demonstration techniques offer an alternative approach to selecting methods for English language learning. Through the implementation of these techniques, there is an expectation that English learning will become more interactive, thereby engaging students' interest.